Attenuated interoceptive processing in individuals with major depressive disorder and high repetitive negative thinking. (December 2022) - Park, Heekyeong; Sanchez, Stella M.; Kuplicki, Rayus; Tsuchiyagaito, Aki; Khalsa, Sahib S.; Paulus, Martin P.; Guinjoan, Salvador M.
Abstract: Repetitive negative thinking (RNT) is a transdiagnostic symptom associated with poor outcomes in major depressive disorder (MDD). MDD is characterized by altered interoception, which has also been associated with poor outcomes. The present study investigated whether RNT is directly associated with altered interoceptive processing. Interoceptive awareness toward the heart and stomach was probed on the Visceral Interoceptive Attention (VIA) task with fMRI in MDD individuals who were propensity-matched on the severity of depression and anxiety symptoms and relevant demographics but different in RNT intensity (High RNT [H-RNT, n = 48] & Low RNT [L-RNT, n = 49]), and in matched healthy volunteers (HC, n = 27). Both H-RNT and L-RNT MDD individuals revealed reduced stomach interoceptive processing compared to HC in the left medial frontal region and insular cortex (H-RNT: β = −1.04, L-RNT: β = −0.97), perirhinal cortex (H-RNT: β = −0.99, L-RNT: β = −1.03), and caudate nucleus (H-RNT: β = −1.06, L-RNT: β = −0.89). However, H-RNT was associated with decreased right medial temporal lobe activity including the hippocampus and amygdala during stomach interoceptive trials (β = −0.61) compared to L-RNT. Insular interoceptive processing was similar in H-RNT and L-RNT participants (β = −0.07, p = 0.92). MDD individuals with high RNT exhibited altered gastric interoceptive responses in brain areas that are important for associating the information with specific contexts and emotions. Attenuated interoceptive processing may contribute to RNT generation, non-adaptive information processing, action selection, and thus poor treatment outcome.